Dynamic soil container and sand pluviator for 1g seismic load tests on anchored retaining wall - Carvalho, A. T. (2010)
In this article the design and setup of the experimental facilities for 1g physical modelling of the seismic behaviour of multi-anchored retaining walls with a one dimensional shaking is addressed. The retained soil will be sand. The facility is composed by an already existing shaking table, a flexible container, a translational sand pluviator and the control and instrumentation hardware. The multiple design criteria that justified the adoption of an Equivalent Shear Beam type for the soil model container are introduced and discussed. The new sand pluviator will allow the preparation of homogenous soil deposits in horizontal directions with relative densities between 70% and 85%, a minor density variation in the vertical direction. The dynamic characteristics of the container and of the container with the model in were studied by a Rayleigh vibration analysis. Finally, the instrumentation setup is described with some detail.